2010
DOI: 10.1007/s00535-010-0245-1
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-33 expression is specifically enhanced in inflamed mucosa of ulcerative colitis

Abstract: IL-33, derived from colonic SEMFs, may play an important role in the pathophysiology of UC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
186
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 219 publications
(194 citation statements)
references
References 31 publications
(41 reference statements)
6
186
0
1
Order By: Relevance
“…In the investigation of IL-33 in colonic diseases, it has been found that the increase of IL-33 is related to the development of colorectal chronic inflammation (ulcerative colitis) (29,30), whereas the epidemiological studies from different countries have revealed that ulcerative colitis may significantly raise the CRC risk (33)(34)(35)(36)(37)(38)(39). Our current study, in our best knowledge, is the first study to demonstrate a dynamic change of IL-33 from the colorectal adenomas to the sporadic CRCs.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In the investigation of IL-33 in colonic diseases, it has been found that the increase of IL-33 is related to the development of colorectal chronic inflammation (ulcerative colitis) (29,30), whereas the epidemiological studies from different countries have revealed that ulcerative colitis may significantly raise the CRC risk (33)(34)(35)(36)(37)(38)(39). Our current study, in our best knowledge, is the first study to demonstrate a dynamic change of IL-33 from the colorectal adenomas to the sporadic CRCs.…”
Section: Discussionmentioning
confidence: 56%
“…In human HCC, no significant difference in IL-33 serum levels was found in HCC compared to liver cirrhosis and healthy controls (28). The role of IL-33 in inflammatory bowel diseases has been studied, extensive evidence now suggests that IL-33 is activated in the inflamed mucosa of ulcerative colitis and plays a critical role in the development of chronic inflammation (29,30), which is a risk factor for CRC. However, information is still very limited regarding the IL-33/ST2 axis in sporadic colorectal tumor-bearing hosts, particularly regarding the changes in the colorectal adenoma-carcinoma sequence.…”
Section: Introductionmentioning
confidence: 99%
“…IL-33 expression was significantly elevated in active lesions from patients with UC, but was not detected in inactive lesions in UC patients or in lesions from patients with either active or inactive Crohn's disease. IL-33 is specifically enhanced in inflamed mucosa of UC, and may play an important role in the pathophysiology of UC (33).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory bowel diseases (IBDs), including ulcerative colitis (UC) and Crohn's disease (CD), are chronic and relapsing intestinal disorders of unknown etiology (1)(2)(3)(4)(5). There is currently no pharmaceutical cure for IBD, and hence treatment options aim for inducing and maintaining remission.…”
Section: Introductionmentioning
confidence: 99%